Africa RISING in Ghana: Impact brief - Azzarri, Carlo; Boukaka, Sedi Anne; Vitellozzi, Sveva (International Food Policy Research Institute, 2024)
The Africa RISING project in Ghana was implemented in 25 communities across the Upper East, Upper West, and Northern regions. The project supported the promotion of early maturing maize varieties and maize-cowpea intercropping, optimal crop spacing for increased groundnut yield, and maize-leaf stripping for livestock feed. It also aimed to foster the adoption of improved feeding for livestock to boost manure production, reduce animal mortality, and increase animal reproduction rates. Alongside these interventions, Africa RISING promoted effective natural resource management (leaf stripping, manure production, and use of nitrogen fertilizer). Mechanization for postharvest handling was also supported, especially the use of fuel-powered maize-shelling machines.